Teacher Views About Intuition and Estimation as Ways of Informal Mathematics - (:unkn) unknown (SAGE Publications Ltd, 2010)
The main purpose of this research was to investigate what kindergarten and primary teachers think about intuition and estimation as a way of mathematics knowing in educational settings. Most of the teachers believed that they should encourage children to do intuitional thinking and estimations in kindergarten and primary settings. However, more grade 6–8 mathematics teachers believe that they should not encourage children to do intuitional thinking and estimations in kindergarten level and primary level than preschool and grade 1–5 classroom teachers. Fewer grade 6–8 mathematics teachers indicated that they got children to ‘always or often’ make estimations than kindergarten and grade 1–5 classroom teachers. Also, more kindergarten teachers believed that there was no difference according to gender in both intuitional and estimational skills. Teachers who perceived themselves as ‘quite practical’ were the ones who encouraged children to do intuitional thinking and estimations ‘always or often’. © 2010 A B Academic Publishers Printed in Great Britain.